Addressing contemporary challenges & future prospects - Kayadibi, Saim; Buang, Ahmad Hidayat (Mehir Vakfi, 2009)
On 17-18 December 2008, 19-20 Zulhijjah 1429 H, an International Seminar on Research in Islamic Studies 2008 (ISRIS’08) opened in Academy of Islamic Studies, University of Malaya in Kuala Lumpur, Malaysia. Participants included researchers, academicians, scholars, postgraduate students, all academic staff of APIUM, and representatives of Selangor State Government, Yayasan Taqwa, Majlis Agama Islam Wilayah Persekutuan, Zekât Board of Selangor, Syariah court of Aceh, as well as some media groups. Members of the academic board of the University of Malaya were also in attendance. Ninety of the participants have given a presentation in three di#erent sessions that were consisted of four or Five parallel sessions held simultaneously. The poster presentation sessions and competitions contributed a colorful environment for the seminar. It was lasted for two days discussed within the seminar contemporary challenges and future prospects of every Field of Islamic studies from Islamic law & comparative law; Islamic property planning and management; Islamic science and civilization; Dakwah and globalization; Islamic banking and finance; Islamic economics; Sufism and Islamic philosophy; Islamic research methodology; Qur’anic hadith studies to Islamic education were some topics of the sessions.